Impact of Organizational Injustice on Employee’s Performance: A Mediating Role of Organizational Commitment - Fatima, Kaneez; Ghoto, Meer Hassan; Ali, Mashooque (The journal of contemporary issues in business and government, 2021)
Organizational commitment is very basic and important factor that has been researched from many years. This study is aimed at the assessment of the impacts of organizational commitment on the performance of employees for which different variables were measured. Thus, both the Qualitative and Quantitative methods were adopted to meet the objective of the study. The study was done on the performance of the health sector workers at the civil hospital of Shaheed Benazirabad (old Nawabshah). Almost 222 respondents containing 197 medical and whereas 25 administrative staff were taken for filling out the questionnaire. The respondents were both genders including 135 male and the rest of them were their female counterparts. The findings of the study have brought to the surface that there was a negative relationship between organizational injustice, employees‟ performance and mediating role of organizational commitment. Mostly organizations compensate employees on the basis of favoritism, managers and supervisors treat their subordinates unfairly, unfair decision making and abusive behavior cause organizational injustice that impacts totally negative on employees‟ performance and organizational commitment. The study findings showed that unethical behavior with employees declines performance and damages an organizational commitment. So, it is very important that organizations should treat their employees with positive and fair attitude, organizational justice is very important factor that can motivate employees to be loyal towards their job. It is recommended that there is a dire need of this type to be executed more within the health sectors of Sindh (very great if in Pakistan) in the upcoming days, so the health sector may have the greater chances of being refurbished at the best.